Manifestations of Gender Injustice in Divorced Marriages: The Kabalutan Tradition - Susi Susilawati; Baliana Amir; Muhammad Ikbal; Rafika Nur; Sitti Fatimah Maddusila (Universitas Negeri Gorontalo, 2023)
This research entitled